Germany's three-pillar banking system : cross-country perspectives in Europe - Brunner, Allan [et al.] (IMF WashingtonUS, 2004)
Looks at the performance of German banks and some of the challenges that lie ahead. Compares them with those of other countries in Europe. Reflects on the role of the public sector in the German banking system and on how the structure can be adapted to changed circumstances.